Friedrich Pollock : The Éminence Grise of the Frankfurt School - Lenhard, Philipp, (Historical Materialism Book Series ;, 2024)
The son of an industrialist who wanted to abolish private property. A Jew who didn't want anything to do with Judaism. A professor who published little. An economist who squandered his wealth on the stock market. A communist who thought Marxism